An Improved Representation of Aerosol Wet Removal by Deep Convection and Impacts on Simulated Aerosol Vertical Profiles. Issue 13 (1st July 2021) - Shan, Yunpeng; Liu, Xiaohong; Lin, Lin; Ke, Ziming; Lu, Zheng
Abstract: We introduce a physics‐based aerosol wet removal scheme with unified treatments of aerosol transport and removal by convective clouds into the Community Atmosphere Model version 6. Since several important physical processes are still neglected or poorly represented in this new physics‐based scheme, we develop secondary improvements to the parameterizations of aerosol activation, resuspension, and cloud‐borne aerosol detrainment in this new scheme. Changes in the aerosol wet removal scheme cause tropospheric aerosol concentrations to decrease to different extents: compared to the control run, the physics‐based scheme significantly decreases aerosol burdens by up to 60% over the southern Pacific Ocean, whereas the secondary improvements mitigate the decreasing tendency. The burden changes also depend on aerosol chemical components: the sulfate mass decrease is compensated by secondary production, black carbon (BC) is effectively removed via increasing the hygroscopicity of particulate organic matter from 0 to 0.2, and dust shows the most spatially heterogeneous changes. Simulated aerosol profiles are evaluated against aircraft‐based observations over the Pacific and Atlantic Oceans. The secondary‐improved scheme reduces the overestimations of upper tropospheric BC and sea salt concentrations by a factor of 10 and 1, 000, respectively, and reproduces the dependence of BC mass decrease rates on cloud types. Consideration of convective cloud‐borne aerosol detrainment plays the most important role in enhancing the aerosol wet removal and decreasing the positive biases of tropospheric BC and sea salt concentrations. We also summarize unresolved issues related to convective cloud genesis and microphysics, cloud‐borne aerosol evolution, and BC and dust emissions. Key Points: Aerosol wet removal by deep convective clouds significantly impacts global aerosol vertical profiles Explicit convective cloud microphysics in wet removal scheme reduces overestimation of black carbon and sea salt concentrations in upper troposphere Parameterization of cloud‐borne (activated) aerosol detrainment from convective clouds to stratiform clouds is an important step in improving the model performance